“Desejáveis” e “indesejáveis”: diferencialidades e paradoxos no acolhimento de venezuelanos/as em Roraima e no Amazonas - Vasconcelos, Iana dos Santos (Universidade Federal de São Carlos, 2021)
This thesis analyzes multiple relationships and institutions involved in the reception processes for Venezuelan migrants in the cities of Boa Vista and Manaus, based on intermittent field research from 2016 to 2020. Migrant reception is marked by a complexity of perspectives, interests, disputes and power games. The measures range between repressive mechanisms and so-called humanitarian actions, sometimes occurring simultaneously. A perceived humanitarian crisis mobilizes secular and mostly religious non-governmental institutions, international organizations and Brazilian Armed Forces that strive daily to make Venezuelans desirable to Manauara and Boa Vista public opinion. But these institutions activities depend directly on the Venezuelans` condition of victims and vulnerable, being perceived as a problem by the locals and becoming undesirable. Being a desirable or undesirable migrant does not imply a fixed position, but corresponds to negotiations that may show differentialities. The agency of the migrant stands out in showing itself to be pendejo (fool) or arrecho (angry). Brazilian hospitality to Venezuelans reveals the paradoxes of a double commitment between welcoming and keeping order. It is concluded that Brazil follows a trend in the global governance of vulnerabilities, sustained in two axes: on the one hand, a transnational ideology of humanitarianism; on the other, concerns about the national security agenda and the alignment with an increasing militarization of international cooperation initiatives.
"Desirable" and "undesirable": differentialities and paradoxes in Venezuelan migrant reception in Roraima and Amazonas
Keywords: Venezuelanos; Humanitarismo; Securitização; Manaus (AM); Boa Vista (RR); Venezuelans; Humanitarianism; Securitization; Manaus (Brazil); CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA